Uncertainties in Transport Project Evaluation: Editorial - Bang Salling, Kim; Nielsen, Otto Anker (European Journal of Transport and Infrastructure Research, 2015)
This following special issue of the European Journal of Transport Infrastructure Research (EJTIR) containing five scientific papers is the result of an open call for papers at the 1st International Conference on Uncertainties in Transport Project Evaluation that took place at the Technical University of Denmark, September 2013. The conference was held under the auspices of the project ‘Uncertainties in transport project evaluation’ (UNITE) which is a research project (2009-2014) financed by the Danish Strategic Research Agency. UNITE was coordinated by the Department of Transport of the Technical University of Denmark (DTU Transport) and carried out in cooperation with several Danish and international partners.